Survival outcomes analysis according to mismatch repair status in locally advanced rectal cancer patients treated with neoadjuvant chemoradiotherapy - Chen, Lin; Yang, Xudong; Zhang, Yuanyuan; Liu, Jie; Jiang, Qixin; Ji, Fang; Gao, Jinli; Zhou, Zhuqing; Wang, Hao; Huang, Jun; Fu, Chuangang (Frontiers in Oncology, 2022)
Abstract Background: The predictive role of mismatch repair (MMR) status for survival outcome and the sensitivity in neoadjuvant chemoradiotherapy settings for patients with locally advanced rectal cancer (LARC) has been inconclusive. Methods: A retrospective cohort of LARC patients treated with neoadjuvant chemoradiotherapy (nCRT) was recruited. After adjusting for baseline characteristics, we used the propensity score matching method to reduce the effect of potential confounding factors with MMR status. Primary analysis was based on overall survival as a more important clinical endpoint. Results: This study included 269 patients. Patients with defective MMR (dMMR) were younger (58.5% vs. 60.0%, p=0.0274) and had lower body mass indices (p=0.0091), higher differentiation grades (p=0.0889), and more advanced rectal cancer (clinical T4 or T4b, p=0.0851; M1, p=0.0055) than those with proficient MMR (pMMR). However, the propensity score-matched patients with dMMR (p=0.0013) exhibited a superior overall survival, even in the M1 subgroup. More importantly, Patients with proficient MMR who undergoing early pathological downstaging, especially lymph node pathological downstaging, can achieve a similar prognosis to patients with dMMR. Conclusion: The clinical significance of this retrospective study mainly includes three points: (1) Data from our study confirmed that LARC patients with dMMR status had better overall survival rates after nCRT, even in M1 subgroup. (2) Similar survival outcomes to patients with early lymph node pathological downstaging, whatever dMMR or pMMR in older and female population. (3) In spite of currently emerging interest in immunotherapy, the traditional neoadjuvant chemoradiotherapy is still an effective treatment for responsive patients with pMMR, considering the extremely low proportion of dMMR population.